Immunogenicity and Toxicity of Different Adjuvants Can Be Characterized by Profiling Lung Biomarker Genes After Nasal Immunization - Sasaki, Eita; Asanuma, Hideki; Momose, Haruka; Furuhata, Keiko; Mizukami, Takuo; Hamaguchi, Isao (Frontiers in Immunology, 2020)
The efficacy of vaccine adjuvants depends on their ability to appropriately enhance the immunogenicity of vaccine antigens, which is often insufficient in non-adjuvanted vaccines. Genomic analyses of immune responses elicited by vaccine adjuvants provide information that is critical for the rational design of adjuvant vaccination strategies. In this study, biomarker genes from the genomic analyses of lungs after priming were used to predict the efficacy and toxicity of vaccine adjuvants. Based on the results, it was verified whether the efficacy and toxicity of the tested adjuvants could be predicted based on the biomarker gene profiles after priming. Various commercially available adjuvants were assessed by combining them with the split influenza vaccine and were subsequently administered in mice through nasal inoculation. The expression levels of lung biomarker genes within 24 h after priming were analyzed. Furthermore, we analyzed the antibody titer, cytotoxic T lymphocyte (CTL) induction, IgG1/IgG2a ratio, leukopenic toxicity, and cytotoxicity in mice vaccinated at similar doses. The association between the phenotypes and the changes in the expression levels of biomarker genes were analyzed. The ability of the adjuvants to induce the production of antigen-specific IgA could be assessed based on the levels of Timp1 expression. Furthermore, the expression of this gene partially correlated with the levels of other damage-associated molecular patterns in bronchoalveolar lavage fluid. Additionally, the changes in the expression of proteasome- and transporter-related genes involved in major histocompatibility complex class 1 antigen presentation could be monitored to effectively assess the expansion of CTL by adjuvants. The monitoring of certain genes is necessary for the assessment of leukopenic toxicity and cytotoxicity of the tested adjuvant. These results indicate that the efficacy and toxicity of various adjuvants can be characterized by profiling lung biomarker genes after the first instance of immunization. This approach could make a significant contribution to the development of optimal selection and exploratory screening strategies for novel adjuvants.